Postnatal Left Ventricular Diastolic Function After Fetal Aortic Valvuloplasty - Friedman, Kevin G. (2011)
Fetal aortic balloon valvuloplasty (FAV) has shown promise in altering in utero progression of aortic stenosis to hypoplastic left heart syndrome. In patients who achieve a biventricular circulation after FAV, left ventricular (LV) compliance may be impaired. Echocardio-graphic indexes of diastolic function were compared between patients with biventricular circulation after FAV, congenital aortic stenosis (AS), and age-matched controls. In the neonatal period, patients with FAV had similar LV, aortic, and mitral valve dimensions but more evidence of endocardial fibroelastosis than patients with AS. Patients with FAV underwent more postnatal cardiac interventions than patients with AS (p = 0.007). Mitral annular early diastolic tissue velocity (E′) was lower in patients with FAV and those with AS and controls in the neonatal period and over follow-up (p <0.001). Septal E′ was similar among all 3 groups in the neonatal period. In follow-up patients, with FAV had lower septal E′ than patients with AS or controls (p <0.001). Early mitral inflow velocity/E′ was higher in patients with FAV as neonates and at follow-up (p <0.001). Mitral inflow pulse-wave Doppler-derived indexes of diastolic function were similar between groups. In conclusion, echocardiographic evidence of LV diastolic dysfunction is common in patients with biventricular circulation after FAV and persists in short-term follow-up. LV diastolic dysfunction in this unique population may have important implications on long-term risk of left atrial and subsequent pulmonary hypertension.